Pengaruh loyalitas pengguna aplikasi iPusnas di kalangan mahasiswa Diploma 3 Perpustakaan FKIP Universitas Tanjungpura terhadap minat membaca buku digital - Benny Harmyanto; Atiqa Nur Latifa Hanum; Sahidi Sahidi (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2023)
This research was conducted to determine the level of loyalty and interest in reading digital books among Diploma 3 students of the FKIP Library of Tanjungpura University and to determine the effect of loyalty on interest in reading digital books among Diploma 3 students of the FKIP Library of Tanjungpura University. This study uses a quantitative approach so that the data collected can be processed specifically. The population in the study amounted to 58 people, namely all active students in the environment of the Diploma 3 Library study program at FKIP Tanjungpura University. The sample was selected using saturated sampling technique or cencus. Data collection in this study was by semi-structured interviews and then followed by distributing questionnaires to the sample. Value measurement on data results using a Likert scale. The validity test used 30 samples using the Pearson Correlation method. The data analysis technique uses the mean formula followed by the grand mean formula from the overall average. While hypothesis testing is done with simple linear regression tests and product moment correlation tests. The research shows the results that iPusnas application user loyalty has a positive and significant impact on interest in reading digital books